Ответ:
a)
b)
c)
d)
e)x=4
f)x=-4
Пошаговое объяснение:
x-7=±6
x-7=-6
x-7=6
x=1
x=13
4x-5=±7
4x-5=-7
4x-5=7
x=3
x-4=±
x-=-3
x-=3
x=-3+4
x=3+4
x+33=±1
x+33=-1
x+33=1
x=-34
x=-32
e)6x-24=0
6x=24
x=4
f)6x+24=0
6x=-24
x=-4
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
a)![x_{1}=1, x_{2}=13 x_{1}=1, x_{2}=13](https://tex.z-dn.net/?f=x_%7B1%7D%3D1%2C%20x_%7B2%7D%3D13)
b)![x_{1}=-\frac{1}{2}, x_{2}=3 x_{1}=-\frac{1}{2}, x_{2}=3](https://tex.z-dn.net/?f=x_%7B1%7D%3D-%5Cfrac%7B1%7D%7B2%7D%2C%20x_%7B2%7D%3D3)
c)![x_{1}=-3\sqrt{5}+4, x_{2}=3\sqrt{5}+4 x_{1}=-3\sqrt{5}+4, x_{2}=3\sqrt{5}+4](https://tex.z-dn.net/?f=x_%7B1%7D%3D-3%5Csqrt%7B5%7D%2B4%2C%20x_%7B2%7D%3D3%5Csqrt%7B5%7D%2B4)
d)![x_{1}=-34, x_{2}=-32 x_{1}=-34, x_{2}=-32](https://tex.z-dn.net/?f=x_%7B1%7D%3D-34%2C%20x_%7B2%7D%3D-32)
e)x=4
f)x=-4
Пошаговое объяснение:
a)![(x-7)^{2}=36 (x-7)^{2}=36](https://tex.z-dn.net/?f=%28x-7%29%5E%7B2%7D%3D36)
x-7=±6
x-7=-6
x-7=6
x=1
x=13
b)![(4x-5)^{2}=49 (4x-5)^{2}=49](https://tex.z-dn.net/?f=%284x-5%29%5E%7B2%7D%3D49)
4x-5=±7
4x-5=-7
4x-5=7
x=3
c)![(x-4)^{2}=45 (x-4)^{2}=45](https://tex.z-dn.net/?f=%28x-4%29%5E%7B2%7D%3D45)
x-4=±![3\sqrt{5} 3\sqrt{5}](https://tex.z-dn.net/?f=3%5Csqrt%7B5%7D)
x-=-3![\sqrt{5} \sqrt{5}](https://tex.z-dn.net/?f=%5Csqrt%7B5%7D)
x-=3![\sqrt{5} \sqrt{5}](https://tex.z-dn.net/?f=%5Csqrt%7B5%7D)
x=-3
+4
x=3
+4
d)
x+33=±1
x+33=-1
x+33=1
x=-34
x=-32
e)6x-24=0
6x=24
x=4
f)6x+24=0
6x=-24
x=-4